The Oxford Companion to American Theatre - Bordman, Gerald Martin; Hischak, Thomas S. (Oxford University Press, 2004)
A guide to the American stage from its beginnings to the present. Includes entries on playwrights, plays, actors, directors, producers, songwriters, famous playhouses, dramatic movements, classic works, commercially successful plays, and foreign figures that have influenced American dramatic development.
Title from home page (Oxford University Press, viewed Oct. 11, 2005).
Keywords: Drama.; Fürstliches Schauspielhaus -- Bad Pyrmont; Universidad Sergio Arboleda; Theater -- United States -- Dictionaries.; Theater -- United States -- Biography -- Dictionaries.; American drama -- Dictionaries.; Theater -- United States.; Théâtre -- États-Unis.; Théâtre (Genre littéraire); Théâtre -- États-Unis -- Biographies -- Dictionnaires anglais.; plays (performing arts compositions); drama (literary genre); PERFORMING ARTS -- Theater -- History & Criticism.; Drama; American drama; Theater; United States; Dramatiker; Schauspieler; USA; Toneel.; Théâtre (Spectacle); Théâtre américain (Littérature); Comédien.; États-Unis.; theater; theatre; uitvoerende kunsten; performing arts; drama; uitvoerend kunstenaars; performers; naslagwerken; reference works; vs; usa; Arts (General); Kunst (algemeen); dictionaries.; collective biographies.; Biographies; Dictionaries; Dictionaries.; Biographies.; Répertoire (Descripteur de forme); Dictionnaire (Descripteur de forme); Dictionnaires.